Customer participation, value co-creation and customer loyalty – A case of airline online check-in system. (September 2016) - Chen, Ching-Fu; Wang, Jing-Ping
Abstract: Information communication technologies and self-service technologies, such as self-check-in kiosks or online check-in systems, are widely used in the air transport industry. This study proposes a conceptual model to investigate the relationships among customer participation, co-created values and customer loyalty in an air transport context, and empirically tests the model by using questionnaire survey data collected from Taiwanese airline passengers. In particular, three perceived values (i.e. enjoyment value, economic value and relational value) are specified to represent the passengers' co-created values. The empirical results support the following hypotheses. Customer participation in using an online check-in system is positively related to all three values, which further lead to satisfaction with respect to the system. System satisfaction is also related to satisfaction with respect to the company, and both system satisfaction and company satisfaction have positive effects on customer loyalty. Highlights: Customer participation and value co-creation of air passengers using online check-in system are examined. Customer participation has positive effects on economic, relational and enjoyment values. Co-created values have positive effects on customer satisfaction and then customer loyalty. System satisfaction is positively related to customer satisfaction.